2013
DOI: 10.2131/jts.38.847
|View full text |Cite
|
Sign up to set email alerts
|

A Study for collecting background data on Wistar Hannover [Crl:WI(Han)] rats in embryo-fetal development studies - comparative data to Sprague Dawley rats -

Abstract: The purpose of the present study was to collect the background data on Wistar Hannover [Crl:WI(Han)] (hereafter Wistar Han) rats in embryo-fetal development studies from the 6 safety research facilities of pharmaceutical companies and contract research organizations. In each facility, 20 or 22 female rats were dosed with vehicle solution during the organogenesis period. As a result, no abnormalities in clinical signs and necropsy findings in dams were found. Body weights and food consumption in dams were lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The numbers of corpora lutea, implantations, and live fetuses tended to be lower in Wistar Hannover rats than in SD rats, as did their ranges. These results are in good agreement with those of previous studies . Fetal weights varied among laboratories and were dependent on the gestational day of cesarean section.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The numbers of corpora lutea, implantations, and live fetuses tended to be lower in Wistar Hannover rats than in SD rats, as did their ranges. These results are in good agreement with those of previous studies . Fetal weights varied among laboratories and were dependent on the gestational day of cesarean section.…”
Section: Resultssupporting
confidence: 92%
“…The incidence of supernumerary ribs was higher in Wistar Hannover rats than that in Crl:CD(SD) rats, in agreement with previous findings. [7][8][9][10][11] The types and incidence of skeletal variation in both Crl:CD (SD) rats (Tables S15A and S15B) and Wistar Hannover rats (Table S16) did not differ between this and the previous surveys.…”
Section: Skeletal Variationsmentioning
confidence: 55%
See 2 more Smart Citations
“…Thoracolumbar supernumerary ribs (TSRs) have been classified as less severe skeletal anomalies, with a relatively high spontaneous incidence in rat fetuses. [1][2][3][4] Current historical control data in Japan have shown that the spontaneous incidence of TSR is 0.09% to 15.1% in Sprague-Dawley (SD) rats, and 17.8% to 58.1% in Wistar Hannover rats. 2 TSR can also be induced in rodent fetuses by maternal stress, 5 maternal hypoglycemia, 6 and exposure to chemicals and herbs during pregnancy.…”
Section: Introductionmentioning
confidence: 99%